Handedness and performance variability as factors influencing mirror movement occurrence - Armatas, C A; Summers, J J; Bradshaw, J L (Journal of clinical and experimental neuropsychology, 1996)
A finger flexion task was used to investigate the effect of hand preference and performance variability on intensity of mirror movement. Right- and left-handed subjects were asked to maintain target forces, with either their index or small finger, that represented 25, 50, or 75% of their maximum strength capacity for the active finger. Greater mirror movement occurred when the small finger was active, and where there was greater variability in task performance, while mirror movement intensity was less when the dominant hand and the index finger were active. These findings were consistent with the cortical activation explanation of motor overflow (Todor & Lazarus, 1986a), and suggest that task variability is an important factor influencing motor overflow production. It was concluded that, if performance variability reflects the efficiency of cortical activation underlying control of a voluntary task, then refined cortical control decreases the potential for motor overflow to occur. However, it is necessary to clarify the relationship between hand preference, performance variability, and motor overflow, perhaps by examining the neural pathways involved in motor overflow production.